2007
DOI: 10.1111/j.1751-1097.2007.00194.x
|View full text |Cite
|
Sign up to set email alerts
|

Diblock Copolymer Micelles Deliver Hydrophobic Protoporphyrin IX for Photodynamic Therapy

Abstract: Polymeric micelles are emerging as an effective drug delivery system for hydrophobic photosensitizers in photodynamic therapy (PDT). The objective of this study was to investigate the formulation of hydrophobic protoporphyrin IX (PpIX) with MePEG(5000)-b-PCL(4100) [methoxy poly (ethylene glycol)-b-poly (caprolactone)] diblock copolymers and to compare their PDT response to that of free PpIX. The photophysical and photochemical properties of the polymeric PpIX micelles were studied by measuring absorbance and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
64
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(69 citation statements)
references
References 50 publications
5
64
0
Order By: Relevance
“…These systems show higher intracellular accumulation of the drug and higher photocytotoxicity in comparison to free PpIX [55]. Similar results were reported for phthalocyanines [96,97].…”
Section: Nano Pdt Passive Nanoparticlessupporting
confidence: 84%
See 2 more Smart Citations
“…These systems show higher intracellular accumulation of the drug and higher photocytotoxicity in comparison to free PpIX [55]. Similar results were reported for phthalocyanines [96,97].…”
Section: Nano Pdt Passive Nanoparticlessupporting
confidence: 84%
“…PS can be modified by encapsulated them in delivery agents such as liposomes [54], micelles [55,56,57,58], ceramic based nanoparticles [59], gold nanoparticles [60,61], and polymer nanoparticles [62]. Liposomes, for example, are able to encapsulate hydrophobic as well as hydrophilic drugs.…”
Section: 'Nano' Strategies For Photosensitizermentioning
confidence: 99%
See 1 more Smart Citation
“…Aggregated structures possess low quantum yields of light absorption and cause significantly less singlet oxygen production. Li et al investigated the formulation of hydrophobic protoporphyrin IX (PpIX) with methoxy PEG-b-PCL micelles and compared their PDT response to that of free PpIX [416]. Fluorescence microscopy revealed that the subcellular localization of free PpIX and PpIX formulated in micelles was similar.…”
Section: Photodynamic Therapymentioning
confidence: 99%
“…19 In the current study, we obtained micelles with a particle size smaller than the reported values. 21,22 This may be attributed to longer PEG chains and the lower molecular weight of the copolymer. The diameter of micelles depends largely on the hydrophilic/hydrophobic chain ratio, and higher PEG/PCL chain ratios produce smaller micelle diameters.…”
Section: Discussionmentioning
confidence: 99%